Analysis of factors influencing postoperative refractive status in patients with high myopia undergoing combined surgery for vitreous opacity and cataract - Yajun Wu; Junrong Liang; Jiasong Yang; Xiaolin Xie; Hua Fan; Wensheng Li (PLoS ONE, 2026)
Aim To observe the postoperative efficacy and factors affecting refractive status following combined vitrectomy and cataract surgery for high myopia (HM) with cataract and vitreous opacities, and compare the differences in refractive status between eyes with and without posterior capsulotomy. Method Retrospective case study, a total of 57 patients (81 eyes) diagnosed with HM complicated with cataracts and vitreous opacity at Shanghai Aier Eye Hospital between 01/01/2022 and 01/01/2025.were included in the study, who underwent pars plana vitrectomy (PPV) combined with cataract phacoemulsification and intraocular lens (IOL) implantation. Preoperative examinations included best corrected visual acuity (BCVA), IOL-master, and Pentacam, with IOL power calculated using the Barrett formula. Postoperative follow-up was conducted at 3 months, including BCVA and refraction assessment. Besides, compared and analyzed the refractive status of eyeballs with and without posterior capsule incision during surgery(60 eyes with posterior capsulotomy and 21 eyes with posterior capsule preservation). Results The mean axial length (AL) of patients’ eyes was 29.77 ± 2.55 mm, and the mean preoperative BCVA was 0.64 ± 0.60 (LogMAR). Three months postoperatively, the mean BCVA improved to 0.40 ± 0.43 (LogMAR), showing a statistically significant improvement (P < 0.05). The mean postoperative spherical equivalent (SE) was −2.83 ± 1.57 degree (D), with an average deviation of −0.23 ± 0.55 (D) from the target refraction. The refractive deviation of all eyes was −0.23 ± 0.55D, and −0.20 ± 0.56D in the posterior capsulotomy group, which was less than −0.30 ± 0.53D in the posterior capsule preservation group compared with the target refractive deviation(p = 0.49). In addition, preoperative SE, postoperative SE, and reserved diopter were significantly correlated with postoperative refractive deviation (r = 0.37,p = 0.0007;r = 0.24,p = 0.03;r = 0.61,p < 0.0001), while age and anterior chamber depth (ACD) were respectively correlated with refractive deviation (r = 0.16,p = 0.22; r = −0.10,p = 0.39). Conclusion Combined surgery for HM with cataract and vitreous opacities improves postoperative vision. The mean deviation between reserved refraction and target refraction is less than 0.5 D. Refractive deviation is significantly correlated with preoperative/postoperative SE and reserved degree, may have a positive correlation with age,and may be negatively correlated with ACD. Posterior cystectomy may also be one of the influencing factors in reducing refractive deviation.